Acute Colonic Pseudo-Obstruction with Feeding Intolerance in Critically Ill Patients: A Study according to Gut Wall Analysis. (12th March 2017) - Zhao, Chenyan; Xie, Tingbin; Li, Jun; Cheng, Minhua; Shi, Jialiang; Gao, Tao; Xi, Fengchan; Shen, Juanhong; Cao, Chun; Yu, Wenkui
Abstract : Objective . To compare the differences between acute colonic pseudo-obstruction (ACPO) with and without acute gut wall thickening. Methods . ACPO patients with feeding tolerance were divided into ACPO with no obvious gut wall thickening (ACPO-NT) group and ACPO with obvious acute gut wall thickening (ACPO-T) group according to computed tomography and abdominal radiographs. Patients' condition, responses to supportive measures, pharmacologic therapy, endoscopic decompression, and surgeries and outcomes were compared. Results . Patients in ACPO-T group had a significantly higher APACHE II (11.82 versus 8.25, p = 0.008 ) and SOFA scores (6.47 versus 3.54, p < 0.001 ) and a significantly higher 28-day mortality (17.78% versus 4.16%, p = 0.032 ) and longer intensive care unit stage (4 versus 16 d, p < 0.001 ). Patients in ACPO-NT group were more likely to be responsive to supportive treatment (62.50% versus 24.44%, p < 0.001 ), neostigmine (77.78% versus 17.64%, p < 0.001 ), and colonoscopic decompression (75% versus 42.86%, p = 0.318 ) than those in ACPO-T group. Of the patients who underwent ileostomy, 81.25% gained benefits. Conclusions . ACPO patients with gut wall thickening are more severe and are less likely to be responsive to nonsurgical treatment. Ileostomy may be a good option for ACPO patients with gut wall thickening who are irresponsive to nonsurgical treatment.